2001
DOI: 10.1124/mol.59.2.349
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a G Protein-Coupled Receptor for Nicotinic Acid

Abstract: Nicotinic acid is a lipid-lowering agent widely used to treat hypertriglyceridemia and to elevate low high density lipoprotein levels. However, the underlying mechanisms are poorly understood. In this study, G protein activation by nicotinic acid and derivatives was assessed as stimulation of guanosine 5Ј-(␥-[

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
2
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 31 publications
(28 reference statements)
7
93
2
2
Order By: Relevance
“…The increases in [Ca 2 þ ] i were concentration dependent in the range of 10 À7 -10 À3 M (Figure 2a). Furthermore, triggering of changes in [Ca 2 þ ] i were caused by NA binding to its specific receptor because nicotinamide, a structurally related compound, which does not bind to GPR109A receptors, 12 (Figure 2c). These data suggested that all mature neutrophils express functional GPR109A receptors and also excluded the possibility that the NA-mediated effects on [Ca 2 þ ] i seen using the bulk spectrofluorometric assay were due to GPR109A-expressing contaminating cells.…”
Section: Resultsmentioning
confidence: 99%
“…The increases in [Ca 2 þ ] i were concentration dependent in the range of 10 À7 -10 À3 M (Figure 2a). Furthermore, triggering of changes in [Ca 2 þ ] i were caused by NA binding to its specific receptor because nicotinamide, a structurally related compound, which does not bind to GPR109A receptors, 12 (Figure 2c). These data suggested that all mature neutrophils express functional GPR109A receptors and also excluded the possibility that the NA-mediated effects on [Ca 2 þ ] i seen using the bulk spectrofluorometric assay were due to GPR109A-expressing contaminating cells.…”
Section: Resultsmentioning
confidence: 99%
“…The membranes were prepared as previously described [71][72][73]. Briefly, cerebella were dissected and homogenized in nine volumes of ice-cold 0.32 M sucrose with a glass Teflon homogenizer.…”
Section: -Nitrophenylcarbamic Acid Cyclohexyl Ester (52)mentioning
confidence: 99%
“…The animals lived in a 12-h light/12-h dark cycle (lights on at 0700 h), with water and food available ad libitum. The rats were decapitated, 8 h after lights on (1500 h), whole brains were removed, dipped in isopentane on dry ice and stored at À80 C. Membranes were prepared as previously described [60][61][62].…”
Section: Animals and Preparation Of Rat Cerebellar Membranes For Mgl mentioning
confidence: 99%